SPE Annual Technical Conference and Exhibition 2010
DOI: 10.2118/135110-ms
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Whirl Detector Aids Drilling Optimization

Abstract: This paper describes the design, development and use of a real-time downhole whirl detection system employed in a latest generation point-the-bit rotary steerable system (Figure 1 shows the general arrangement of the steering system). The system employs a novel yet simple whirl detection sensor design which is sensitive to whirl yet passively filters out lateral vibration. Test results presented include full-scale BHA testing in a whirl simulation rig in conjunction with field trials at a drilling test facilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…As experience continued, it was realized that the most common mode of vibration-related tool failure is backward whirl. Further computer modeling and addition fullscale laboratory simulations were employed to develop and qualify a new onboard sensor, which is able to detect the presence of backward whirl and provide a real-time indication of its intensity (Minett-Smith, Stroud & Pagett, 2010). This device is capable of supplying real-time alerts as wells as detailed memory data for further interpretation.…”
Section: Evolution Of the Systemmentioning
confidence: 99%
“…As experience continued, it was realized that the most common mode of vibration-related tool failure is backward whirl. Further computer modeling and addition fullscale laboratory simulations were employed to develop and qualify a new onboard sensor, which is able to detect the presence of backward whirl and provide a real-time indication of its intensity (Minett-Smith, Stroud & Pagett, 2010). This device is capable of supplying real-time alerts as wells as detailed memory data for further interpretation.…”
Section: Evolution Of the Systemmentioning
confidence: 99%
“…Full-scale laboratory tests and downhole drilling tests have exhibited loading frequencies in the range of 6-30 times the drill-string rotation rate (Minett-Smith et al, 2010). Figure 2 shows actual test results illustrating the motion of the drillstring centerline under backward whirl.…”
Section: Dangers Of Backward Whirlmentioning
confidence: 99%
“…Different BHA whirl types have been identified using transverse bending-moment sensors and transverse magnetometers (Close et al 1988;Shyu 1989;Vandiver et al 1990;Macpherson et al 2001). Other researchers have used two sets of accelerometers in a rotary steerable system (RSS) to detect and quantify collar/stabilizer whirl (Minett-Smith et al 2010). Using the same sensor, Stroud et al (2011) showed the motion of the collar in transition from "rolling-sliding" to "backward whirl" in laboratory testing.…”
Section: Introductionmentioning
confidence: 99%